Clinical-epidemiological Characterization of Patients with a First Event of Atrial Fibrillation - Víctor Manuel Regal Cuesta; Lázaro Enrique de la Cruz Avilés; Aymara Marcia Hernández Cardoso; Fransisco de Jesús Valladares Carvajal; Liz María Calvo Díaz; Milagros Lisset León Regal (Revista Finlay)
Foundation: despite the importance of the first event of atrial fibrillation as one of the most treated medical emergencies, in Cienfuegos, there are insufficient studies describing the clinical-epidemiological characteristics of these patients. Objective: to clinically and epidemiologically characterize patients with the first event of atrial fibrillation in Cienfuegos between the years 2020-2022. Method: a descriptive and cross-sectional study was carried out. The universe was made up of 54 patients diagnosed with a first event of atrial fibrillation admitted to the Cardiology Service of the Dr. Gustavo Aldereguía Lima General University Hospital in Cienfuegos between the years 2020-2022. The variables studied were: age, sex, skin color, toxic habits, personal pathological history, clinical manifestations, echocardiographic parameters and treatment. The absolute and relative frequencies of the variables were calculated. The results were presented in tables. Results: the male sex, the age group of 36-55 years, white skin color, and smoking predominated. The most common personal pathological history was: high blood pressure (74.1 %), type 2 diabetes mellitus (16.7 %) and valvular heart disease (11.1 %). The most frequent clinical manifestations were: palpitations (77.8 %), followed by dyspnea (12.9 %). Echocardiographic parameters were within the normal range. Pharmacological treatment was applied to 68.5 % followed by pharmacological and electrical cardioversion in 16.7 %. Conclusions: the largest number of patients with a first event of atrial fibrillation have a structurally healthy heart, so the prevention of recurrences is considered of vital importance, this will avoid the creation of electrical and anatomical conditions that perpetuate the arrhythmia.